Teachers' Perception on the Implementation of Zoom Cloud Meeting in Online English Learning - Savitri, Ni Luh Astri; Ibrahim, Moh. Syahrun; Umar, Irmawaty (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This Research was focused on analyzing the teachers' perception on the implementation of Zoom Cloud Meeting in online English learning at SMP Negeri 3 Gorontalo. This research designed to find out what teachers' perception on the implementation of Zoom Cloud Meeting in online English learning. This research applied descriptive qualitative method. The data of the research has been collected by using an interview and it was analyzed based on thematic analysis. The total numbers of participants of this research were 3 English teachers who already have experience in implementing Zoom Cloud Meeting in online English learning. Based on the result, it was found that the teachers had both negative and positive responses. While the teacher showed with a positive response. The teachers assumed that Zoom Cloud Meeting can facilitate and improve the competence in learning English. Although there are some problems that encountered, but they can solve it if there is communication between teacher and students. In conclusion, most of the participants agreed about the implementation of Zoom Cloud Meeting as a media of learning considering the advantages of the platforms that help them in learning English through online during the pandemic of covid-19.